2007
DOI: 10.1021/ja073902+
|View full text |Cite
|
Sign up to set email alerts
|

Deducing the Energetic Cost of Protein Folding in Zinc Finger Proteins Using Designed Metallopeptides

Abstract: Zinc finger transcription factors represent the largest single class of metalloproteins in the human genome. Binding of Zn(II) to their canonical Cys4, Cys3His1, or Cys2His2 sites results in metal-induced protein folding events required to achieve their proper structure for biological activity. The thermodynamic contribution of Zn(II) in each of these coordination spheres toward protein folding is poorly understood because of the coupled nature of the metal-ligand and protein-protein interactions. Using an uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
154
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(178 citation statements)
references
References 78 publications
23
154
0
Order By: Relevance
“…pH, buffer, direct titration or competition experiments). As pointed out by the studies of Mely et al [36] and Gibney et al, [12,14,30] as a consequence of the competition between metal and protons, the pH-dependence of the apparent metal binding constant must be investigated to fully describe the coordination properties (species formed and binding constants) of the cysteine-contaning peptides. The protonation state of cysteines in ZnA C H T U N G T R E N N U N G (Cys) 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…pH, buffer, direct titration or competition experiments). As pointed out by the studies of Mely et al [36] and Gibney et al, [12,14,30] as a consequence of the competition between metal and protons, the pH-dependence of the apparent metal binding constant must be investigated to fully describe the coordination properties (species formed and binding constants) of the cysteine-contaning peptides. The protonation state of cysteines in ZnA C H T U N G T R E N N U N G (Cys) 4 …”
Section: Discussionmentioning
confidence: 99%
“…For example, the cost of the folding of CCHH zinc fingers is still subject to debate in spite of a high number of studies. [13,14] Small molecular models of protein metal sites constitute a viable tool to gain insights into the metal/protein interactions. [15] Determining the energy contributions of these interactions is crucial to understand metal-induced protein folding and design de novo metalloproteins.…”
Section: The Origin Of This Stabilisation Is As-a C H T U N G T R E Nmentioning
confidence: 99%
See 1 more Smart Citation
“…So the overall folding involves a delicate interplay of hydrophobic packing, hydrogen bonding, and metal binding (Li et al, 2007(Li et al, , 2008. In addition, if the coordination residues are located on flexible terminals or loops, as in BABZ2 and BABZ4, zinc binding-induced aggregation may occur, especially for the small protein like βαβ, so the entropy cost to fix the coordination residues at specific conformations should be considered, as zinc binding in proteins is an entropy-driven process (Reddi et al, 2007). It has been demonstrated that the primary interactions are enough to produce potentially useful zinc binding affinity (Wade et al, 1993), and this agrees with our design work.…”
Section: Discussionmentioning
confidence: 99%
“…After Zn 2+ was added, the channel was activated showing an obvious increase in ion conductance. Zinc finger proteins shrank to finger-like conformations, thus enlarged the effective pore size [58]. Appropriate opening size of nanochannel is necessary for a successful zinc biosensor.…”
Section: Ion Sensorsmentioning
confidence: 99%